2016
DOI: 10.1002/mame.201600138
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Conjugated Microporous Polymers Bearing Pyrazine Moieties with Macroscopically Porous 3D Networks Structures

Abstract: The N‐containing conjugated microporous polymers (CMPs) are synthesized by 2,5‐dibromopyrazine or its isomeric pyridazine monomer and 1,3,5‐triethynylbenzene via the Pd(0)/Cu(I)‐catalyzed Sonogashira–Hagihara cross‐coupling polycondensation. The resulting CMPs exhibit diverse porosity and morphology, which reveals macroscopically porous 3D networks for BQCMP‐1, agglomerated and amorphous structure for DQCMP‐1, arising from the variation of isomeric monomer. In addition, metal ions adsorption capacity of Zn(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…20,21 Also, the high designable flexibility of CMPs makes it possible to exquisitely control both the chemical nature and desired porosity of CMPs by simply varying the molecular structure or chemical constitution of CMP building blocks. [22][23][24][25] Previous studies have proven that both the desired porous features of absorbents and high affinity of host materials to iodine would enhance the iodine uptakes of a porous absorbent. [17][18][19] We have demonstrated that the choice of both monomer structures and solvents should lead to different morphology or pore structures.…”
mentioning
confidence: 99%
“…20,21 Also, the high designable flexibility of CMPs makes it possible to exquisitely control both the chemical nature and desired porosity of CMPs by simply varying the molecular structure or chemical constitution of CMP building blocks. [22][23][24][25] Previous studies have proven that both the desired porous features of absorbents and high affinity of host materials to iodine would enhance the iodine uptakes of a porous absorbent. [17][18][19] We have demonstrated that the choice of both monomer structures and solvents should lead to different morphology or pore structures.…”
mentioning
confidence: 99%
“…In this work, we used two multitopic monomers possessing different geometries, namely tetrakis(4-ethynylphenyl)methane and 1,3,5-triethynylbenzene, as the structural units for PPPhs synthesis by the Diels-Alder polycondensation reaction with bulky phenylene-substituted bis(cyclopentadienone)s. Previously, the aforementioned ethynyl-containing compounds were used in the POP synthesis by Sonogashira-Hagihara cross-coupling and Yamamoto polymerization reactions, yielding crosslinked insoluble products [15,17,41,42]. Our approach results in soluble polyphenylenes with SSA up to 751 m 2 /g, which could be effectively controlled during the synthesis.…”
Section: Introductionmentioning
confidence: 97%
“…On the one hand, silver-based zeolites or aerogels not only have limited available surface areas (low uptake of I 2 ) but also their high cost and adverse environmental impact make these compounds less suitable for I 2 capture. On the other hand, conjugated microporous polymers (CMPs) or porous organic polymers (POPs) show excellent iodine capture due to the presence of a number of N-containing species, at 75–80 °C and at ambient pressure. But a cumbersome synthesis due to the nonavailability of the monomers is not applicable on an industrial scale.…”
Section: Introductionmentioning
confidence: 99%